Reaksi pasar dan kinerja keuangan perusahaan sebelum dan sesudah pengumuman right issue pada perusahaan yang melakukan right issue di bursa efek indonesia - Kurniawan, Indra Suyoto; Yasha, Emelda (JURNAL MANAJEMEN, 2016)
This research is using technique purposive sampling that obtained sample counted 41 companies. Data are derived from capital market directory for firms that issuing right for the year 2009,2010, 2011 and 2012. The analysis uses statistical examination constructively SPSS program 21. In analyzing to be used paired sample T test. Result of Hypothesis testing indicates that : (1) there was no significant abnormal returns before and after the announcement of the rights issue; (2) Current ratio statistically not significant before and after the announcement of the rights issue; (3) Debt to Equity ratio statistically significant before and after the announcement of the rights issue; (4) Return on Investment ratio statistically not significant before and after the announcement of the rights issue; (5) Asset Turnover ratio statistically not significant before and after the announcement of the rights issue; (6) Price Earnings ratio statistically not significant before and after the announcement of the rights issue.Keyword: Right Issue, Abnormal Return, Financial Performance